2015
DOI: 10.1159/000367661
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Decreases Intra-Abdominal Adhesion Formation in a Rat Model

Abstract: Aim: The purpose of this study was to investigate the effectiveness of honokiol, a natural molecule that was shown to have antioxidant effects, in prevention of intra-abdominal adhesion formation in a rat model. Material and Method: This study was conducted on a total of 40 non-pregnant Sprague-Dawley rats, which were divided into 4 groups as follows: sham, control, saline, and honokiol groups. Both uterine horns of the rats in control, saline, and honokiol groups were exposed and a 2-cm segment of the anti-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the rat intra-abdominal adhesion model generated by electrocautery to injure the peritoneum [25], Montalvo-Jave EE and colleagues used an anti-adherence compound consisting of a sodium hyaluronate and carboxymethylcellulose gel to reduce the degree of inflammatory infiltration and the number of adhesion lesions. Additionally, some natural compounds with anti-inflammatory and anti-oxidative actions, such as honokiol [26] and bromelain [27], also have effects on preventing the formation of intra-abdominal adhesions, to a certain extent. Our previous studies [16] also verified that adhesion formation in rat models can be prevented using anti-inflammatory drugs, such as selective COX-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat intra-abdominal adhesion model generated by electrocautery to injure the peritoneum [25], Montalvo-Jave EE and colleagues used an anti-adherence compound consisting of a sodium hyaluronate and carboxymethylcellulose gel to reduce the degree of inflammatory infiltration and the number of adhesion lesions. Additionally, some natural compounds with anti-inflammatory and anti-oxidative actions, such as honokiol [26] and bromelain [27], also have effects on preventing the formation of intra-abdominal adhesions, to a certain extent. Our previous studies [16] also verified that adhesion formation in rat models can be prevented using anti-inflammatory drugs, such as selective COX-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen radicals (ROS) formed during hypoxia activate fibroblasts, causing the production of cytokines such as vascular endothelial growth factor (VEGF), tissue growth factor (TGF), and cyclooxygenase-2, which all increase adhesion formation [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol, a biologically active substance derived from the bark of magnolia trees, has been shown to exert significant anti-inflammatory, antioxidative, antitumour and neuroprotective effects [31][32][33]. Agacayak et al [34] found that treatment with 1 mg/kg honokiol for 14 days was effective in prevention of PAA in a rat model. It may be related to its effects of anti-inflammatory and antifibrosis because the inflammation score and fibrosis score are significantly lower in the honokiol group compared with the saline group in the study.…”
Section: Honokiolmentioning
confidence: 99%